Advances focusing on the application of decellularization methods in tendon-bone healing - Sheng Zhong; Yujian Lan; Jinyu Liu; Man Seng Tam; Zhipeng Hou; Qianghua Zheng; Shijie Fu; Dingsu Bao (Journal of Advanced Research, 2025)
Background: The tendon or ligament is attached to the bone by a triphasic but continuous area of heterogeneous tissue called the tendon-bone interface (TBI). The rapid and functional regeneration of TBI is challenging owing to its complex composition and difficulty in self-healing. The development of new technologies, such as decellularization, has shown promise in the regeneration of TBI. Several ex vivo and in vivo studies have shown that decellularized grafts and decellularized biomaterial scaffolds achieved better efficacy in enhancing TBI healing. However further information on the type of review that is available is needed. Aim of the review: In this review, we discuss the current application of decellularization biomaterials in promoting TBI healing and the possible mechanisms involved. With this work, we would like to reveal how tissues or biomaterials that have been decellularized can improve tendon-bone healing and to provide a theoretical basis for future related studies. Key scientific concepts of the review: Decellularization is an emerging technology that utilizes various chemical, enzymatic and/or physical strategies to remove cellular components from tissues while retaining the structure and composition of the extracellular matrix (ECM). After decellularization, the cellular components of the tissue that cause an immune response are removed, while various biologically active biofactors are retained. This review further explores how tissues or biomaterials that have been decellularized improve TBI healing.